Qualitative Study of the Relationship between Ergonomics and Psychological Factors on Work Productivity - Frisdyanto, Wigi; Jabar , Abdul; Sanjaya , Fahri Muhamad Fatih; Prayoga , Aerio Widi; Umerah , Putri Nadia (Review: Journal of Multidisciplinary in Social Sciences, 2025)
This qualitative study discusses the relationship between ergonomic application and psychological factors in relation to work productivity. In various industrial and organizational contexts, ergonomics has been shown to reduce physical and mental workload, ultimately improving employee comfort and performance. On the other hand, psychological factors such as work stress, job satisfaction, motivation, and social relationships significantly influence employees' perception of their productivity. By analyzing literature from 15 national and international journals, this study finds that ergonomic approaches integrated with attention to psychological aspects lead to positive impacts on productivity. The study suggests that organizations should not only focus on the physical aspects of job design but also the mental and emotional well-being of employees holistically.